(untitled) (Journal of Comilla Medical College Teachers’ Association, 2026)
Background: Memory is a crucial component of our daily lives. Thus, its deterioration should be managed. In this regard, pharmacological treatments have become less favourable due to their prolonged duration and numerous adverse effects. Phyllanthus emblica (PE) may be a suitable substitute because of its diverse biological functions, cost efficiency, lower toxicity and easy accessibility. Objective: To evaluate the alleviative role of ethanolic extract of Phyllanthus emblica (EEPE) fruit on memory. Methods: This study was performed at the KM Farid uddin Animal Research Laboratory, Department of Physiology, BMU, involving 24 male Long-Evans rats (8±2 weeks; 225±75 gm). On the basis of treatments, all rats (6 rats/group) were grouped into normal control (NC), sham control (SC), colchicine control (ColC), post-colchicine Phyllanthus emblica treatment (Post PE Exp). A single dose of colchicine (15 µg) caused memory impairment and Morris water maze (MWM) was used to test for learning and memory. Results: Here, in Reference memory performance colchicine caused significantly higher mean escape latency (EL) (p≤0.001) in acquisition phase and average EL of 5th and 6th acquisition days (p≤0.01) as well as significantly (p≤0.001) lower target crossings (TC) and time spent in target (TT) in ColC rats in comparison to those SC rats. In contrast, significantly lower mean EL (p≤0.001) in acquisition phase and average EL of 5th and 6th acquisition days (p≤0.05) along with significantly higher TC and TT (p≤0.001) were found in Post PE Exp rats, in comparison to those of ColC rats. In working memory test, colchicine also caused significantly higher mean EL (p≤0.001) in training and test phase in ColC rats, in comparison to those SC rats. However, our experimental (Post PE Exp) rats showed significantly (p≤0.001) lower mean EL when compared to those of ColC rats. Moreover, when we compared all these memory variables between our experimental and NC rats, they were found statistically non-significant. Conclusion: The study revealed that Phyllanthus emblica (Amloki) may be an encouraging therapeutic option for mitigating the neurotoxicity associated with colchicine; however, more studies are needed to define the exact mechanism through which PE functions. J Com Med Col Teachers’ Asso Jan 2026; 30(1): 09-15